Bacterial and Fungal Profiles as Markers of Infliximab Drug Response in Inflammatory Bowel Disease. (10th December 2020) - Ventin-Holmberg, Rebecka; Eberl, Anja; Saqib, Schahzad; Korpela, Katri; Virtanen, Seppo; Sipponen, Taina; Salonen, Anne; Saavalainen, Päivi; Nissilä, Eija
Abstract: Background and Aims: Inflammatory bowel diseases [IBDs], Crohn's disease [CD] and ulcerative colitis [UC], are globally increasing chronic gastro-intestinal inflammatory disorders associated with altered gut microbiota. Infliximab [IFX], a tumour necrosis factor [TNF]-alpha blocker, is used to treat IBD patients successfully, though one-third of the patients do not respond to therapy. No reliable biomarkers are available for prediction of IFX response. Our aims were to investigate the faecal bacterial and fungal communities during IFX therapy and find predictors for IFX treatment response in IBD patients. Methods: A total of 72 IBD patients [25 CD and 47 UC] started IFX therapy and were followed for 1 year or until IFX treatment was discontinued. An amplicon sequencing approach, targeting the bacterial 16S rRNA gene and fungal ITS 1 region separately, was used to determine the microbiota profiles in faecal samples collected before IFX therapy and 2, 6, and 12 weeks and 1 year after initiation of therapy. The response to IFX was evaluated by colonoscopy and clinically at 12 weeks after initiation. Results: Both faecal bacterial and fungal profiles differed significantly between response groups before start of IFX treatment. Non-responders had lower abundances of short chain fatty acid producers, particularly of the class Clostridia, and higher abundances of pro-inflammatory bacteria and fungi, such as the genus Candida, compared with responders. This was further indicated by bacterial taxa predicting the response in both CD and UC patients [area under the curve >0.8]. Conclusions: Faecal bacterial and fungal microbiota composition could provide a predictive tool to estimate IFX response in IBD patients.